In The House of Tom Bombadil: A Traumatic Healing Therapy at Home - Reynaldi Christian Yapto; Juanda (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
A trauma can be healed with several methods, which one of the simplest method to be done with patients who suffers such condition is a psychological healing treatment at home. This treatment, although its very simple to be done, can positively impact the traumatic person’s behaviour in a future ahead.  A fictional example of healing treatment at home can be found in Tom Bombadil's actions against the Hobbits found in The Lord of the Rings: The Fellowship of The Ring. There, Tom Bombadil executed a healing treatment at his house towards the hobbits to heal them from their traumatic events that they experienced in the past. The crucial part of this treatment at the Tom Bombadil’s house would change these hobbits characters and behaviour in the following events. This essay will try to describe one of the psychological therapies to apply to people with traumatic symptoms by learning through the actions of Tom Bombadil. The results of this study will show how Tom Bombadil's healing therapy for hobbits represent the simplest yet propitious psychological treatment to applied